2020
DOI: 10.1017/ssh.2020.42
|View full text |Cite
|
Sign up to set email alerts
|

Generations of Veterans: Socioeconomic Attainment from World War II to the Contemporary Era

Abstract: Scholars have long examined how generations or, more technically, cohorts produce social change. According to theory, people’s lives are shaped by the years in which they were born because they experience, along with their peers, particular historical events at the same points in the life course. Despite the importance of history, however, many scholars have evaluated cohorts not defined by clear start and end dates, but rather by arbitrary cut points, such as five-year intervals. In contrast, this article use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…As mentioned earlier, there is controversy about the effect of military experience on earnings. Scholars found that military service during World War II boosted the income of U.S. veterans (e.g., Angrist & Krueger, 1994; De Tray, 1982; MacLean & Kleykamp, 2021; Smith et al, 2012), while Vietnam-era veterans earned less (e.g., Angrist, 1990; Spiro et al, 2016; Teachman & Call, 1996). Even so, most of prior studies affirmed the positive effects of military service on the earnings of some socially disadvantaged groups, such as minorities, rural people, and women (Angrist, 1998; Hou et al, 2020; Padavic & Prokos, 2017; Sheehan & Hayward, 2019), because military service tends to help them gain access to elite jobs and narrow gaps in human and social capital.…”
Section: Theoretical Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, there is controversy about the effect of military experience on earnings. Scholars found that military service during World War II boosted the income of U.S. veterans (e.g., Angrist & Krueger, 1994; De Tray, 1982; MacLean & Kleykamp, 2021; Smith et al, 2012), while Vietnam-era veterans earned less (e.g., Angrist, 1990; Spiro et al, 2016; Teachman & Call, 1996). Even so, most of prior studies affirmed the positive effects of military service on the earnings of some socially disadvantaged groups, such as minorities, rural people, and women (Angrist, 1998; Hou et al, 2020; Padavic & Prokos, 2017; Sheehan & Hayward, 2019), because military service tends to help them gain access to elite jobs and narrow gaps in human and social capital.…”
Section: Theoretical Hypothesesmentioning
confidence: 99%
“…On the other hand, the advantages of veterans are also reflected in enjoying better social welfare and medical resources (Angrist, 1998; Davies et al, 2015; Oh & Berry, 2021; Waller & McGuire, 2011), having more competitive military skills (Johansen et al, 2014; Lindqvist & Vestman, 2011; MacLean, 2017), improving personal qualities and abilities (Angrist & Chen, 2011; Brown & Routon, 2016; Eynde, 2015; L. Wang et al, 2012), obtaining higher socioeconomic status (e.g., Angrist & Krueger, 1994; Bachman et al, 2000; Brown & Routon, 2016; MacLean & Kleykamp, 2021; Sheehan & Hayward, 2019; Smith et al, 2012), and accumulating political resources (Diamant, 2008; Hou et al, 2020; Wakenhut, 1979; Wu & Treiman, 2004). Hence superior external conditions seem to make veterans have better health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Financially, veterans' earnings relative to civilian peers are sometimes higher and sometimes lower depending on cohort effects and time (MacLean & Kleykamp, 2021). However, among some studies showing lower income among veterans, these differences are reduced or eliminated among Black veterans (Cooney et al, 2003; Kleykamp, 2013).…”
Section: Factors Of Transition Successmentioning
confidence: 99%